2017
DOI: 10.1080/17435390.2017.1343404
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle interactions with co-existing contaminants: joint toxicity, bioaccumulation and risk

Abstract: With their growing production and application, engineered nanoparticles (NPs) are increasingly discharged into the environment. The released NPs can potentially interact with pre-existing contaminants, leading to biological effects (bioaccumulation and/or toxicity) that are poorly understood. Most studies on NPs focus on single analyte exposure; the existing literature on joint toxicity of NPs and co-existing contaminants is rather limited but beginning to develop rapidly. This is the first review paper evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(112 citation statements)
references
References 156 publications
0
110
0
2
Order By: Relevance
“…Limited data of multiple NPs exposure is available [55]. The results of this study show that CeO 2 NP yielded an antagonistic cytotoxicity on TiO 2 NP, but more evident effects were observed for the longer exposure period, where the mixture toxicity was altered.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Limited data of multiple NPs exposure is available [55]. The results of this study show that CeO 2 NP yielded an antagonistic cytotoxicity on TiO 2 NP, but more evident effects were observed for the longer exposure period, where the mixture toxicity was altered.…”
Section: Discussionmentioning
confidence: 63%
“…The state-of-the-art shows that combined exposure to multiple chemicals often results in different toxicity to that of the individual substances [55]. Hence, it is imperative to recognize and address the risks from exposure to multiple chemicals in a more systematic way, as consistently drawn attention by the Joint Research Centre (JRC) [56], and Scientific Committee on Health and Environmental Risks (SCHER), Scientific Committee on Consumer Safety (SCCS), Scientific Committee on Emerging and Newly Identified Health Risks (SCENIHR) [57].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of existing contaminants may decrease bioavailability of the active metal ions by complex formation, aggregation, or absorption, thus reducing environmental toxicity; on the other hand, they may have synergistic effects, increasing the ecotoxicological risk [113,114]. Deng et al [115] pointed out that NPs released into water bodies may react with organic contaminants, metal/metalloid ions, dissolved organic matter, inorganic ligands and other NPs, as well as influencing the bioaccumulation of organic contaminants and heavy metal ions. Zhang et al [116] reported that TiO 2 NPs had a synergistic inhibitory effect with atrazine against the alga Chlorella pyrenoidosa, an additive effect with pentachlorobenzene, and an antagonistic effect for hexachlorobenzene and 3,3′,4,4′-tetrachlorobiphenyl.…”
Section: Np Interactions With Chemical Pollutantsmentioning
confidence: 99%
“…Tong et al suggest that the fate and toxicity potential of soluble ENMs, such as ZnO NPs, are likely to be influenced by the presence of other stable ENMs, such as TiO 2 NPs, the combined effects of ZnO dissolution and Zn adsorption onto TiO 2 NPs control the concentration of dissolved zinc . Actually, there are many great researches about the interaction of nanoparticles, especially when they become pollutants in the environment . It is necessary to investigate the potential side‐effects of these food‐borne NPs on intestinal cells and to mechanistically understand the observed biological responses .…”
Section: Introductionmentioning
confidence: 99%